2020
DOI: 10.3389/fneur.2020.573356
|View full text |Cite
|
Sign up to set email alerts
|

Unfractionated Heparin in SARS-CoV-2 Pneumonia: Ischemic Stroke Case Report

Abstract: Thromboembolism is a known phenomenon in patients with Coronavirus disease 2019 (COVID-19). Recent investigations have revealed that a significant proportion of those hospitalized with severe COVID-19 demonstrate clinical and laboratory markers compatible with hypercoagulability, which is differentiated from disseminated intravascular coagulation (DIC), termed COVID-associated coagulopathy. Additionally, there is increasing concern for development of acute ischemic stroke because of this hypercoagulable state.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, when ACE2 expression is high, the HS coreceptor function is dispensable. Some studies have reported that interferon-mediated induction of ACE2 expression occurs upon SARS-CoV-2 infection (Fu et al, 2020;Su and Jiang, 2020;Tan et al, 2020), suggesting that blocking HS-SV2-S binding by heparin may not be sufficient (Efendizade et al, 2020;Hippensteel et al, 2020;Menezes-Rodrigues et al, 2020) and would need to be combined with other mechanism-based agents to most effectively to treat and/or prevent COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, when ACE2 expression is high, the HS coreceptor function is dispensable. Some studies have reported that interferon-mediated induction of ACE2 expression occurs upon SARS-CoV-2 infection (Fu et al, 2020;Su and Jiang, 2020;Tan et al, 2020), suggesting that blocking HS-SV2-S binding by heparin may not be sufficient (Efendizade et al, 2020;Hippensteel et al, 2020;Menezes-Rodrigues et al, 2020) and would need to be combined with other mechanism-based agents to most effectively to treat and/or prevent COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 71 articles (127 patients) that satisfied the criteria mentioned above were included in this review. In this review, 80 cases of patients developed IS during COVID-19 infection (Aasfara et al 2021 ; Abdulkadir et al 2020 ; Agarwal et al 2020 ; Al-Mufti et al 2021 ; Al Saiegh et al 2020 ; Appavu et al 2021 ; Ashraf and Sajed 2020 ; Avula et al 2020 ; Bessa et al 2020 ; Bigliardi et al 2020 ; Burkert and Patil 2020 ; Co et al 2020 ; Dakay et al 2020a , b ; de Almeida Lima et al 2020 ; de Lorenzo Alvarez et al 2021 ; Deliwala et al 2020 ; Dumitrascu et al 2020 ; Efendizade et al 2020 ; El Nahas et al 2020 ; Elshereye and Erdinc 2020 ; Eskandarani et al 2021 ; Fu et al 2021 ; Garg et al, 2020 ; Gemcioglu et al 2020 ; Goette et al 2020 ; Goldberg et al 2020 ; Guillan et al 2020 ; Iqbal et al 2021 ; Kwon et al 2020 ; Mahboob et al 2020 ; Mansour et al 2020 ; Mirzaee et al 2020 ; Morassi et al 2020 ; Mowla et al 2020 ; Patel et al 2020a , b ; Patel et al 2020a , b ; Prasad et al 2021 ; Priftis et al 2020 ; Rajdev et al 2020 ; Rascón-Ramírez et al 2020 ; Roy et al 2021 ; Valderrama et al 2020 ; Viguier et al 2020 ; Zhai et al 2020 ), 32 cases developed intracranial hemorrhage (Ahmad et al 2021 ; Al-Mufti et al 2021 ; Al Saiegh et al 2020 ; Carroll and Lewis 2021 ; Cezar-Junior et al 2020 ; Dakay et al 2020a , b ; Dakay et al 2020a , ...…”
Section: Resultsmentioning
confidence: 99%